Acute Toxicity of Two Detergents on the Juvenile Climbing Perch (Anabas Testudineus) And Stinging Catfish (Heteropneustes Fossilis) (Bangladesh Journal of Zoology, 2023)
The two commercial household synthetic detergents were used to investigate the mortality and behavioural changes of juvenile Climbing perch (Anabas testudineus) and Stinging catfish (Heteropneustes fossilis). Average weight 2.83 ± 0.10 g and 3.93 ± 0.09g for A. testudineus and average length 3.85 ± 0.12cm and 4.33 ± 0.09cm were recorded for H. fossilis respectively. Acute toxicity tests were determined according to OECD (The Organization for Economic Cooperation and Development) guidelines for 72 hours exposure. Lethal Concentrations (LC10, LC50 and LC95) of both of the test materials were ascertained using probit analysis software (SPSS version 25) at 95% confidence limit. The LC50 values of detergent 1 were 120.4, 87.3, 59.7 mg/L for A. testudineus and 55.5, 31.6 and 24.5 mg/L for H. fossilis at 24h, 48h and 72h respectively. On the other hand, LC50 values of detergent 2 were 173.3, 90.2, 54.2 mg/L for A. testudineus and 44.8, 31.7, 22.0 mg/L for H. fossilis at 24h, 48h and 72h respectively. Toxicity was significantly increased along with exposure period for both fishes under two aquas conditions. H. fossilis was more susceptible than A. testudineus for both detergents. Comparative toxicity studies showed that detergent two was more effective than detergent one (detergent 2 ≥ detergent1). Physical changes such as discoloration in body and gill, damaged fin were also observed after 72h exposure of the both detergents. Behavioural responses in treated group were erratic swimming, restlessness, aggression, hyperactivity, more frequent movements at the bottom. Thus, adverse eco-toxicological impacts of synthetic detergents on fish mortality, behavioural pattern are suspected and suggested more elaborate research on physiological aspects for better understand the environmental impact in future.Bangladesh J. Zool. 51(1): 87-98, 2023